Evaluación de la ingeniería mecatrónica en función del perfil de egreso por áreas del conocimiento / Assessment of Mechatronics Engineering Function the Graduate Profile by Areas of Knowledge - Peña Almaguer, Odilia B.; Villarreal Cárdenas, Sergio (Revista Internacional de Aprendizaje en Ciencia, Matemáticas y Tecnología, 2015)
ABSTRACT The graduate profile of Mechatronics Engineering students at the Instituto Tecnologico de Estudios Superiores de la Region Carbonifera (ITESRC) in Agujita, Coahuila, Mexico marks a clear objective: seeks to train professionals in the creative Mechatronics Engineering. When they graduate, must have analytical and critical capabilities that enable them to design, project, build, innovate and manage computers and mechatronic systems, in the social and productive sector. Also they must be able to integrate, operate and maintain equipment, always with an ethical commitment to quality and a framework of sustainable development. [1] All mentioned requirements, were placed on paper when the career began. Meanwhile, companies are hiring graduates of the specialty, with a desirable professional profile requesting the number of previous skills and some added values, according to their operational needs. This paper sets out explicitly the extent to which it meets the demands of the labor sector, effecting a qualitative research, supported by the focus group techniques and cross-sectional study. The impact of the study is to carry out the necessary adjustments on the graduate profile of Mechatronic Engineer, to achieve a comprehensive training consistent with society needs. What is not measured, it’s not controlled, and the ITESRC wants to keep all in control to give a good education service and the best students for society. RESUMEN El perfil de egreso del alumnado de la carrera de Ingeniería en Mecatrónica del Instituto Tecnológico de Estu-dios Superiores de la Región Carbonífera (ITESRC), ubicado en Agujita, Coahuila, México, marca un objetivo claro: busca formar profesionistas en la Ingeniería Mecatrónica con capacidad analítica, crítica y creativa que les permita diseñar, proyectar, construir, innovar y administrar equipos y sistemas mecatrónicos en el sector social y productivo; así como integrarlos, operarlos y mantenerlos, con un compromiso ético y de calidad en un marco de desarrollo sustentable. (ITESRC, 2013) Por otra parte, las empresas que reciben a los egresados de la especialidad, señalan como perfil profesional deseable la serie de competencias señaladas anteriormente y otros valores agregados, de acuerdo a sus necesidades de operación. En este trabajo se analiza de manera explícita hasta qué punto se cumple con las demandas del sector laboral, efectuando una investigación cualitativa, respaldada por las técnicas focus group y estudio transversal. El propósito del estudio, es la realización de los ajustes precisos al perfil de egreso del ingeniero en Mecatrónica, para lograr una formación integral congruente con las necesidades de la sociedad. Contacto principal: odilia.berenice@hotmail.es